Locoregional recurrence-associated factors and risk-adapted postmastectomy radiotherapy for breast cancer staged in cT1-2N0-1 after neoadjuvant chemotherapy - Wang X; Xu L; Yin Z; Wang D; Wang Q; Xu K; Zhao J; Zhao L; Yuan Z; Wang P (Cancer Management and Research, 2018)
Xin Wang, Liming Xu, Zhenzhen Yin, Daquan Wang, Qi Wang, Kunpeng Xu, Jinlin Zhao, Lujun Zhao, Zhiyong Yuan, Ping Wang Department of Radiation Oncology, Tianjin Medical University Cancer Institute and Hospital, National Clinical Research Center for Cancer, Key Laboratory of Cancer Prevention and Therapy, Tianjin, Tianjin’s Clinical Research Center for Cancer, Key Laboratory of Breast Cancer, Prevention and Therapy, Tianjin Medical University, Ministry of Education, Tianjin, 300060, China Objective: In order to identify risk factors associated with locoregional recurrence (LRR) and assess the role of postmastectomy radiotherapy (PMRT) in early breast cancer (BC), managed with neoadjuvant chemotherapy (NAC) and mastectomy, a retrospective analysis of BC diagnosed with clinical stage T1-2N0-1 was conducted.Patients and methods: A total of 217 patients were included in this analysis. The median age was 50 years (24–72 years). The clinical stage distributions were cT1 in 15 cases, cT2 in 202, cN0 in 53, and cN1 in 161 cases. All patients were treated with NAC and mastectomy, and 128 patients received PMRT.Results: With a median follow-up time of 61 months, the 5-year cumulative LRR rate was 12%. Multivariate analysis demonstrated that pathological N stage, lymph-vascular invasion, and histological grade were independent prognostic factors associated with LRR. A nomogram model based on these factors was established, based on which the patients were deeply stratified into low- and high-risk group. In the low-risk group, radiotherapy did not decrease LRR (3.3% in PMRT group, 1.7% in no PMRT group, P=0.192). While in the high-risk group, PMRT significantly decreased LRR (21.8% in PMRT group, 42.2% in no PMRT group, P=0.031).Conclusion: Lymph-vascular invasion, histological grade, as well as pathological N stage were important prognostic factors associated with LRR in BC patients staged in cT1-2N0-1, who were managed with NAC and mastectomy. In our cohort, not only clinical and pathological stage information but also other risk factors were taken into consideration when adjuvant PMRT was recommended. In the high-risk subgroup, PMRT significantly improved the prognosis. Keywords: breast cancer, neoadjuvant chemotherapy, postmastectomy radiotherapy, prognosis